The search for multiple populations in Magellanic cloud clusters: I.Two stellar populations in the small Magellanic cloud globular cluster NGC 121 - Niederhofer, Florian; Cordero, Maria J. (Arxiv, 2016)
We started a photometric survey using the WFC3/UVIS instrument onboard the Hubble Space Telescope to search for multiple populations within Magellanic Cloud star clusters at various ages. In this paper, we introduce this survey. As first results of this programme, we also present multi-band photometric observations of NGC 121 in different filters taken with the WFC3/UVIS and ACS/WFC instruments. We analyze the colour-magnitude diagram (CMD) of NGC 121, which is the only "classical" globular cluster within the Small Magellanic Cloud. Thereby, we use the pseudo-colour C_(F336W,F438W,F343N)=(F336W-F438W)-(F438W-F343N) to separate populations with different C and N abundances. We show that the red giant branch splits up in two distinct populations when using this colour combination. NGC 121 thus appears to be similar to Galactic globular clusters in hosting multiple populations. The fraction of enriched stars (N rich, C poor) in NGC 121 is about 32% +/- 3%, which is lower than the median fraction found in Milky Way globular clusters. The enriched population seems to be more centrally concentrated compared to the primordial one. These results are consistent with the recent results by Dalessandro et al. (2016). The morphology of the Horizontal Branch in a CMD using the optical filters F555W and F814W is best produced by a population with a spread in Helium of Delta(Y) =0.025+/-0.005.